Involvement of Locus Coeruleus Noradrenergic Neurons in Supraspinal Antinociception by α,β-Methylene-ATP in Rats - Masato Fukui; Azusa Takishita; Nannan Zhang; Takayuki Nakagawa; Masabumi Minami; Masamichi Satoh (Elsevier, 2004)
We reported previously that intracerebroventricular (i.c.v.) administration of P2X-receptor agonists produced antinociception and the effect was attenuated by i.c.v. pretreatment with β2-adrenergic receptor antagonists. The present study examined the involvement of noradrenergic neurons arising from the locus coeruleus (LC) in the supraspinal antinociception by the P2X-receptor agonist α,β-methylene-ATP in rats. We found that pretreatment with DSP-4 (50 mg/kg, i.p.), which is a neurotoxin to selectively disrupt noradrenergic neurons arising from the LC, significantly attenuated the antinociception by i.c.v. administration of α,β-methylene-ATP (10 nmol/rat). Microinjection of α,β-methylene-ATP (0.1 and 1 nmol/side) into the bilateral LC significantly elevated the nociceptive threshold more potently than the i.c.v. administration at a dose of 10 nmol/rat. The antinociception by intra-LC injection of α,β-methylene-ATP (1 nmol/side) was significantly attenuated by co-injection of pyridoxal-phosphate-6-azophenyl-2',4'-disulphonic acid (1 nmol/side), a non-selective P2X-receptor antagonist. These results suggest that noradrenergic neurons arising from the LC are involved in the supraspinal antinociception by α,β-methylene-ATP through P2X receptors in the LC. Keywords:: antinociception, locus coeruleus, α,β-methylene-ATP, DSP-4, P2X receptor